Interaktive Einkaufserlebnisse in Innenstädten

Projekt FLEMING – Predictive Maintenance von zentralen Komponenten des Mittelspannungsnetzes - zur Heiden, Philipp (DASC-PM v1.1 Fallstudien)

Frauensache(n)? Mode und Gender aus feministischer Perspektive. - Haller, Melanie (Tietze, Katharina/Schnittler, Anna-Brigitta: Mode und Gender.)

Der Tod und die Liebe: Die Metaphysik der Kommunikation - Fuchs, Christian (Soziale Ordnungen des Sterbens: Theorie, Methodik und Einblicke in die Vergänglichkeit)

Digital Ethics. Media, Communication and Society Volume Five - Fuchs, Christian

Lebensdauerprognose für Stahlklebverbindungen bei multiaxialer Belastung mit Phasenverschiebung, veränderlicher Mittelspannung und variablen Amplituden - Nagel, Christof; Carillo Beber, Vinicius; Mayer, Bernd; Köster, Christian; Matzenmiller, Anton; Hecht, Matthias; Baumgartner, Jörg; Melz, Tobias; Tews, Karina; Çavdar, Serkan; Meschut, Gerson (23. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Experimental investigation of the fatigue behavior and calculation of the service life of adhesively bonded joints - Tews, Karina; Teutenberg, Dominik; Meschut, Gerson

Nonlinear S-Parameter Behavioral Model of a Photonic Radar Transceiver Chipset for Automotive Applications - Kruse, Stephan; Schwabe, Tobias; Kneuper, Pascal; Meinecke, Marc-Michael; Kurz, Heiko G.; Scheytt, J. Christoph
This paper presents a method to model monolithically integrated photonic radar transceiver (TRX) with optical local oscillator (LO) distribution in silicon germanium (SiGe) electronic photonic integrated circuits (EPICs). The model proposed approximates the behavior of the nonlinear scattering (S)-parameters and noise figure of each building block of the TRX chipset by Laplace polynomials and hyperbolic tangent functions. The modular approach of the model allows to optimize hardware components with respect to the entire TRX system, and fault identification with reduced computational effort. The proposed method is validated using the first monolithically integrated photonic radar transceiver chipset and shows excellent agreement with the post layout simulation results and, including the photodiode (PD) bandwidth (BW) degradation, also with the measurements.

Der digitale Kapitalismus. Arbeit, Entfremdung und Ideologie im Informationszeitalter - Fuchs, Christian

Experimental and numerical investigation of the damping properties of adhesively bonded tubular steel joints - Göddecke, Johannes; Meschut, Gerson; Damm, Jannis; Albiez, Matthias; Ummenhofer, Thomas; Kötz, Fabian; Matzenmiller, Anton (The Journal of Adhesion)

On the structure of regularization paths for piecewise differentiable regularization terms - Gebken, Bennet; Bieker, Katharina; Peitz, Sebastian (Journal of Global Optimization)
Regularization is used in many different areas of optimization when solutions are sought which not only minimize a given function, but also possess a certain degree of regularity. Popular applications are image denoising, sparse regression and machine learning. Since the choice of the regularization parameter is crucial but often difficult, path-following methods are used to approximate the entire regularization path, i.e., the set of all possible solutions for all regularization parameters. Due to their nature, the development of these methods requires structural results about the regularization path. The goal of this article is to derive these results for the case of a smooth objective function which is penalized by a piecewise differentiable regularization term. We do this by treating regularization as a multiobjective optimization problem. Our results suggest that even in this general case, the regularization path is piecewise smooth. Moreover, our theory allows for a classification of the nonsmooth features that occur in between smooth parts. This is demonstrated in two applications, namely support-vector machines and exact penalty methods.

Weaker Quadriceps Corticomuscular Coherence in Individuals Following ACL Reconstruction during Force Tracing - Sherman, David A.; Baumeister, Jochen; Stock, Matt S.; Murray, Amanda M.; Bazett-Jones, David M.; Norte, Grant E. (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

The Mode of Endurance Exercise Influences Changes in EEG Resting State Graphs among High-Level Cross-Country Skiers. - Büchel, Daniel; Torvik, PØ; Lehmann, Tim; Sandbakk, Ø; Baumeister, Jochen (Med Sci Sports Exerc)

Inhibition of Motor Planning and Response Selection after Anterior Cruciate Ligament Reconstruction. - Sherman, DA; Baumeister, Jochen; Stock, MS; Murray, AM; Bazett-Jones, DM; Norte, GE (Med Sci Sports Exerc)

Numerical study of light backscattering from layers of absorbing irregular particles larger than the wavelength - Alhaddad, Samer; Förstner, Jens; Grynko, Yevgen (Journal of Quantitative Spectroscopy and Radiative Transfer)
Keywords: tet_topic_scattering

LoRa Transceiver for Load Monitoring and Control System in Microgrids - Mwammenywa, Ibrahim; Petrov, Dmitry; Holle, Philipp; Hilleringmann, Ulrich (2022 International Conference on Engineering and Emerging Technologies (ICEET))

Adorno and the Media in Digital Capitalism - Fuchs, Christian (Adorno und die Medien: Kritik, Relevanz, Ethik)

Recommendations for managing AI-driven change processes: when expectations meet reality - Stieglitz, Stefan; Möllmann, Nicholas R.J.; Mirbabaie, Milad; Hofeditz, Lennart; Ross, Björn (International Journal of Management Practice)
Artificial intelligence (AI) has moved beyond the planning phase in many organisations and it is often accompanied by uncertainties and fears of job loss among employees. It is crucial to manage employees attitudes towards the deployment of an AI-based technology effectively and counteract possible resistance behaviour. We present lessons learned from an industry case where we conducted interviews with affected employees. We evaluated derived resistance to AI factors in a large-scale (N = 368) survey and found that the deployment of AI-based technologies does not differ from other IT, but that the change is perceived differently due to misguided expectations.

Characterizing Ion Transport in Electrolytes via Concentration and Velocity Profiles - Mistry, Aashutosh; Srinivasan, Venkat; Steinrück, Hans-Georg (Advanced Energy Materials)
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment

Experimental Investigations of Carbon Fiber Reinforced Polymer Composites and Their Constituents to Determine Their Elastic Material Properties and Complementary Inhomogeneous Experiments with Local Strain Considerations - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (Fibers and Polymers)
Abstract Composite materials, such as fiber reinforced polymers, become increasingly important due to their excellent mechanical and lightweight properties. In this respect, this paper reports the characterization of a unidirectional carbon fiber reinforced polymer composite material. Particularly, the mechanical behavior of the overall composite and of the individual constituents of the composite is investigated. To this end, tensile and shear tests are performed for the composite. As a result, statistics for five transversely isotropic material parameters can be established for the composite. For the description of the mechanical properties of the constituents, tensile tests for the carbon fiber as well as for the polymer matrix are carried out. In addition, the volume fraction of fibers in the matrix is determined experimentally using an ashing technique and Archimedes’ principle. For the Young’s modulus of the fiber, the Young’s modulus and transverse contraction of the matrix, as well as the volume fraction of the constituents, statistics can be concluded. The resulting mechanical properties on both scales are useful for the application and validation of different material models and homogenization methods. Finally, in order to validate the obtained properties in the future, inhomogeneous tests were performed, once a flat plate with a hole and a flat plate with semicircular notches.
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Non-local integral-type damage combined to mean-field homogenization methods for composites and its parallel implementation - Lenz, Peter; Mahnken, Rolf (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Student Teachers ’ Knowledge of Congruence before a University Course on Geometry - Hoffmann, Max; Biehler, Rolf (Proceedings of the Fourth Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2022, 19-22 October 2022))
Keywords: Teaching and learning of specific topics in university mathematics; Transition to; across and from university mathematics; Student Teachers; Geometry; Congruence; Double Discontinuity.

Innovations in university teaching based on mathematic education research - Florensa, Ignasio; Hoffmann, Max; Romo Vázquez, Avenilde; Zandieh, Michelle; Martínez-Planell, Rafael (Proceedings of the Fourth Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2022, 19-22 October 2022))

Beep-and-Sleep: Message and Energy Efficient Set Cover - Götte, Thorsten; Kolb, Christina; Scheideler, Christian; Werthmann, Julian (Theor. Comput. Sci.)

Three-dimensional dipole momentum analog based on L-shape metasurface - Li, Tianyou; Chen, Yanjie; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling (Applied Physics Letters)
The achievement of a flat metasurface has realized extraordinary control over light–matter interaction at the nanoscale, enabling widespread use in imaging, holography, and biophotonics. However, three-dimensional metasurfaces with the potential to provide additional light–matter manipulation flexibility attract only little interest. Here, we demonstrate a three-dimensional metasurface scheme capable of providing dual phase control through out-of-plane plasmonic resonance of L-shape antennas. Under circularly polarized excitation at a specific wavelength, the L-shape antennas with rotating orientation angle act as spatially variant three-dimensional tilted dipoles and are able to generate desire phase delay for different polarization components. Generalized Snell's law is achieved for both in-plane and out-of-plane dipole components through arranging such L-shape antennas into arrays. These three-dimensional metasurfaces suggest a route for wavefront modulation and a variety of nanophotonic applications.
Keywords: Physics and Astronomy (miscellaneous)

Supporting Construction and Architectural Visualization through BIM and AR/VR: A Systematic Literature Review - Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 19th IFIP TC13 International Conference on Human-Computer Interaction (INTERACT 2023))

Learning Permutation-Invariant Embeddings for Description Logic Concepts - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (Advances in Intelligent Data Analysis XXI: 21st International Symposium on Intelligent Data Analysis, IDA 2023, Louvain-la-Neuve, Belgium, April 12–14, 2023, Proceedings)
Keywords: dice enexa sail SFB-TRR 318 demir ngonga

Integrating Prospective Scenarios in Life Cycle Engineering: Case Study of Lightweight Structures - Ostermann, Moritz; Grenz, Julian; Triebus, Marcel; Cerdas, Felipe; Marten, Thorsten; Tröster, Thomas; Herrmann, Christoph (Energies)
Lightweight design is a common approach to reduce energy demand in the use stage of vehicles. The production of lightweight materials is usually associated with an increase in energy demand, so the environmental impacts of lightweight structures need to be assessed holistically using a life cycle assessment. To estimate the life cycle environmental impacts of a product in its developmental stage, for example, by life cycle engineering, future changes in relevant influencing factors must be considered. Prospective life cycle assessment provides methods for integrating future scenarios into life cycle assessment studies. However, approaches for integrating prospective life cycle assessment into product development are limited. The objective of this work is to provide the methodological foundation for integrating future scenarios of relevant influencing factors in the development of lightweight structures. The applicability of the novel methodology is demonstrated by a case study of a structural component in a steel, aluminium, and hybrid design. The results show that appropriate decarbonisation measures can reduce the life cycle greenhouse gas emissions by up to 95 percent until 2050. We also found that shifts in the environmentally optimal design are possible in future scenarios. Therefore, the methodology and data provided contribute to improved decision-making in product development.
Keywords: Life Cycle Engineering; Life Cycle Assessment; Lightweight Design; Prospective LCA; Future-oriented LCA; Energy System; Material production; Sustainable production

Digitalität, Mediatisierung und Bildung - Megatrends aus medienpädagogischer Perspektive - Herzig, Bardo (Bildung und Digitalität. Analysen - Diskurse - Perspektiven)

Modellbildung und Modellnutzung in der Allgemeinen Didaktik - Herzig, Bardo (Pädagogische Rundschau. Sackgasse oder Meilenstein? Zur Sinnhaftigkeit von Modellbildungen in der Erziehungswissenschaft)

Kinderstärkende Pädagogik in der Grundschule im Kontext (post-)pandemischer Herausforderungen. Kennzeichen, Kritische Anfragen und Blinde Flecke. Vortrag an der Tagung: Was Resilienz stärkt. Chancen und Risiken eines immer populärer werdenden Konzepts. Pädagogische Hochschule Heidelberg. - Büker, Petra

KrafT: Bildungsdokumentation in der inklusiven Schule partizipativ gestalten. 9. Paderborner Grundschultag zum Thema: „Demokratie Lernen von Anfang an“. Online - Büker, Petra; Herding, Jana; Drexler, Leonie

Near-Term Effects of Short-Term Study Abroad: A Longitudinal Examination of Learner Perceptions - Müller, Mareike (Frontiers: The Interdisciplinary Journal of Study Abroad)
A relatively small body of research has been conducted on the near- and long-term effects of study abroad (SA) to date. This existing research suggests that SA effects on language skills tend to be volatile, while the impact on various aspects of learners’ personal, academic, and professional development may be longer-lasting. Yet, learner perspectives on the dynamics and durability of such effects, in particular in the context of short-term SA programs, remain largely unexplored. This study hence investigates the near-term impact of short-term SA programs as experienced by students within the first months and years following their sojourns. A qualitative case-study design is employed to examine the accounts of four American students of German, who studied abroad in Austria for four weeks and were interviewed repeatedly over a period of up to 40 months after their sojourns. The results suggest that, from the students’ perspective, many effects deteriorate in the near term, although the overall sojourn experience still appears influential. Abstract in German Nur wenige Forschungsvorhaben haben sich bislang den mittel- bis langfristigen Auswirkungen studentischer Auslandsaufenthalte gewidmet; die bisherige Datenlage deutet jedoch darauf hin, dass die Auswirkungen auf sprachliche Kompetenzen eher unbeständig sind, wohingegen die persönliche, studiums- und berufsbezogene Entwicklung der Lernenden länger von einem Auslandsaufenthalt beeinflusst wird. Die Dynamik und Beständigkeit derartiger Auswirkungen wurden jedoch kaum mit Blick auf kurze Auslandsaufenthalte (≤ acht Wochen) sowie aus der Perspektive der Studierenden erforscht, was die vorliegende Studie insbesondere hinsichtlich mittelfristiger Effekte fokussiert. Mittels eines qualitativen Fallstudiendesigns werden die Interviewdaten vier amerikanischer Deutschlernender untersucht, die sich vier Wochen in Österreich aufhielten und in einem Zeitraum von bis zu 40 Monaten nach ihrem Aufenthalt wiederholt befragt wurden. Die Ergebnisse zeigen, dass viele Auswirkungen eines solchen Aufenthalts aus studentischer Perspektive mittelfristig verblassen, auch wenn der Auslandsaufenthalt im Gesamten weiterhin als einflussreiche Erfahrung wahrgenommen wird.

Investigation of change in dispersive behaviour during adhesive curing in multi-layered structures - Zeipert, Henning; von Germeten, Christian; Friesen, Olga; Claes, Leander; Johannesmann, Sarah; Henning, Bernd (Fortschritte der Akustik - DAGA 2023)

Bestimmung der Volumenviskosität mittels akustischer Absorptionsmessung - Claes, Leander (Fortschritte der Akustik - DAGA 2023)

Characterization of adhesion strength using guided ultrasonic waves - Nicolai, Marcel; Zeipert, Henning; Lugovtsova, Yevgeniya; Bulling, Jannis; Johannesmann, Sarah; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2023)

Professionalisierung für Digitale Bildung im Grundschulalter. Ergebnisse des Forschungsprojekts P³DiG
Durch Digitalisierung und Digitalität entstehen neue Fragestellungen für die formale und non-formale Bildung. Insbesondere die Professionalisierung von Lehrkräften und Fachpersonal steht durch die Dynamik der technologischen und kulturellen Entwicklungen vor weitreichenden Herausforderungen. Der vorliegende Band beschäftigt sich mit der Frage der Professionalisierung von Grundschullehrkräften und pädagogischen Fachkräften für eine Digitale Bildung im Grundschulalter und ist auf der Grundlage des BMBF-Projekts Primat des Pädagogischen in der Digitalen Grundbildung – Grundsatzfragen und Gelingensbedingungen in der Professionalisierung von pädagogischen Akteur:innen für Kinder im Grundschulalter, P3DiG, entstanden. Im ersten Teil des Sammelbandes werden Grundlagen der Professionalisierung für eine Digitale Grundbildung dargelegt. Im zweiten Teil werden die Ergebnisse des Projekts präsentiert. Dabei werden sowohl Professionalisierungsmodelle für eine Digitale Grundbildung als auch die Ergebnisse der im Projekt durchgeführten empirischen Untersuchungen zur Digitalen Grundbildung im Grundschulalter vorgestellt. Der Band kann damit als Grundlage für die Ausarbeitung von Professionalisierungskonzepten in Hochschulen, Seminaren und Weiterbildungseinrichtungen dienen und liefert Impulse für die weitere wissenschaftliche Auseinandersetzung.

Room-Temperature Electrical Field-Enhanced Ultrafast Switch in Organic Microcavity Polariton Condensates - De, Jianbo; Ma, Xuekai; Yin, Fan; Ren, Jiahuan; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing; Malpuech, Guillaume; Solnyshkov, Dmitry (Journal of the American Chemical Society (JACS))
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Circularly polarized electroluminescence from a single-crystal organic microcavity light-emitting diode based on photonic spin-orbit interactions - Jia, Jichao; Cao, Xue; Ma, Xuekai; De, Jianbo; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field - Rose, Hendrik; Vasil'ev, A. N.; Tikhonova, O. V.; Meier, Torsten; Sharapova, Polina (Physical Review A)

Instabilities of Polymer Melt Suspensions under Uniaxial Extension (Poster) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Examining the Measurement Invariance and Convergent Validity of the SSIS-SELb-Student in Austria and Germany. 44th Annual Conference of the International School Psychology Association (ISPA) 2023. - Anthony, Christopher J.; Yost, M; Howe, A; Schwab, Susanne; Hassani, Sepideh; Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze

Experimentelle und numerische Untersuchung des Einflusses variabler Betriebstemperaturen auf das Trag- und Versagensverhalten struktureller Klebverbindungen unter Crashbelastung - Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar; Striewe, Marius; Meschut, Gerson (23. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Analysis of temperature effect on strength and microstructure in friction induced recycling process (FIRP) - Borgert, Thomas; Homberg, Werner (Materials Research Proceedings)
Abstract. In order to reduce global energy consumption in production and industry along with the associated CO2 emissions, existing resources must be used more efficiently. This includes the energy-efficient and comprehensive recycling of a wide range of metals. Especially for the production of aluminium, there is a large potential for saving energy using efficient recycling processes. With regard to the recycling of aluminium studies have shown that solid-state recycling processes are significantly more efficient considering the used energy and resources compared to the conventional, smelting-metallurgical recycling process. In this paper, the direct and energy-efficient friction-induced recycling process (FIRP) based on the conform process is further described and analysed in terms of the temperature-property relationships. For this purpose, the influence of the processing temperature on the microstructure and properties of the recycled semi-finished products is investigated using the toll system that enables an ECAP forming. Specific sections of the (in theory) infinite, recycled semi-finished product are taken and analysed at different process temperatures of the solid state recycling process. Based on these sections, the properties in terms of mechanical hardness, strength, ductility and grain size are analysed and a degressive relationship between process temperature and mechanical hardness up to a temperature of 270 °C can be shown. Applying the Hall-Petch relationship, it is analysed whether there is a correlation between the strength and the microstructure in the form of the grain size.
Keywords: Recycling; Aluminium; Friction-Induced; Energy Efficiency

Writing as Narrative Resource in Therapeutic Settings: Diaries, Sketches, Notes - Mildorf, Jarmila; Ketteler, Daniel (Narrative and Mental Health Today: Reimagining Theory and Practice)

Narrative and Mental Health: Reimagining Theory and Practice

Untersuchung überlagerter Effekte von Druckverlust und Totvolumen durch Rekuperation am isobaren Expansionsmotor - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny Y. (Chemie Ingenieur Technik)
Die Wirtschaftlichkeit von Wärmemotoren wird maßgeblich durch die Rückführung von Wärme in Rekuperatoren beeinflusst. Beim isobaren Expansionsmotor vom Bush-Typ, einem Wärmemotor, welcher bereits mit Wärmequellen ab 60°C betrieben werden kann, steigt der thermische Wirkungsgrad durch den Einsatz von Rekuperatoren signifikant. Gleichzeitig wirken sich das Fluidvolumen des Wärmeübertragers sowie der beim Betrieb auftretende Druckverlust negativ auf den thermischen Wirkungsrad aus. In dieser Arbeit wird der Zusammenhang von Totvolumen, Druckverlust und Wärmerückgewinnung untersucht und Empfehlungen für den Betrieb von Rekuperatoren am isobaren Expansionsmotor gegeben.
Keywords: Isobarer Expansionsmotor; Dynamische Wärmeübertragungsmodellierung; Phasenwechsel; dichte Arbeitsmedien

Narratives and Mental Health: An Introduction - Mildorf, Jarmila; Punzi, Elisabeth; Singer, Christoph (Narrative and Mental Health: Reimagining Theory and Practice)

Investigation of the leak tightness of structural adhesive joints for use in battery housings considering mechanical and corrosive loads - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson (The Journal of Adhesion)

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis